Classification of errors in determining trigonometry function values at standard positions - Setiawan, Yayan Eryk Setiawan; Sunardi (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2023)
One of the important materials to study in a trigonometry course is the value of trigonometric functions in standard positions. However, the results of preliminary research show that there are still many first semester students who experience errors in determining the value of the trigonometric function in the standard position. These errors are important for further analysis. Therefore this study aims to describe the mistakes of the first semester students in determining the value of the trigonometric function in the standard position. This type of research is a qualitative descriptive study with a case study approach towards students of the mathematics education study program at a university in Malang. The data collected in this study consisted of the subject's work and transcripts of interviews with the subject. Work data were analyzed descriptively to know the types of student errors. The transcript data from the interview results were analyzed by coding, to determine the factors that caused student error. The results showed that out of 34 students who made errors in determining the value of trigonometric functions at the standard position, 11% had conceptual errors, 56% had principle errors, 15% had calculation errors and 18% had factual errors. The results of this study contribute to teaching the material for the value of trigonometric functions in the standard position to reduce conceptual errors, principle errors, calculatin errors, and factual errors.